2016
DOI: 10.1159/000444304
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Hemostatic Effect of FloSeal in Patients Undergoing Robot-Assisted Laparoscopic Radical Prostatectomy

Abstract: Background: Perioperative bleeding is a potential complication of robot-assisted laparoscopic radical prostatectomy (RALP) that may worsen outcomes. The role of local hemostatic materials in RALP has not been adequately assessed. We evaluated the hemostatic impact of FloSeal (Baxter International Inc., Fremont, Calif., USA) in RALP. Methods: A retrospective analysis was performed of 392 consecutive patients with prostate cancer who underwent RALP at our institution between February 2008 and July 2014. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…e effectiveness of FLOSEAL, which is a topical hemostatic agent containing a flowable gelatin bovine matrix and a human-derived thrombin component, has been shown in various types of operations [1][2][3][4]6,9,11,[13][14][15]16,20] . However, no reports have evaluated the effectiveness of FLOSEAL objectively in the neurosurgical field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e effectiveness of FLOSEAL, which is a topical hemostatic agent containing a flowable gelatin bovine matrix and a human-derived thrombin component, has been shown in various types of operations [1][2][3][4]6,9,11,[13][14][15]16,20] . However, no reports have evaluated the effectiveness of FLOSEAL objectively in the neurosurgical field.…”
Section: Discussionmentioning
confidence: 99%
“…Compounded thrombin then facilitates forming a fibrin clot around the matrix that results in hemostasis. [15] e effectiveness of FLOSEAL has been previously reported in various types of operations, [1][2][3][4]6,9,11,[13][14][15]16,20] and the use of FLOSEAL may shorten the time to achieve hemostasis. [14] However, in neurosurgical operations, few previous reports have shown the utility of FLOSEAL, [1,6] and no reports have evaluated its effectiveness objectively.…”
Section: Introductionmentioning
confidence: 94%
“…These procedures have included prostatectomy, thoracolumbar spinal surgery, thyroidectomy, and dacryocystorhinostomy. [12][13][14][15] Gall at al 16 prospectively studied 18 patients to examine GTHM use for bleeding after postendoscopic sinus surgery. They reported that it is safe and effective for use during and after surgery, and does not affect wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the commercially available bioadhesives and their clinical applications are presented in Table 3. Hemostasis in cardio-vascular surgeries [130][131][132] • Hemostasis in more patients with FloSeal ® than in the control group with a gel foam with thrombin at 3 min • Cessation of bleeding within 10 min of the first lesion was higher with FloSeal ® than in the control group for cardiac surgeries and vascular surgeries • FloSeal ® led to less postoperative bleeding, lower rate of transfusion of blood products • Rates of revision for bleeding and minor complications were not different Hemostasis in spinal surgeries 130,[133][134][135] • Hemostasis achieved in more patients with FloSeal ® than with a gel foam + thrombin at 3 min • Cessation of bleeding within 10 min of the first lesion was higher with FloSeal ® than in the control group for the spinal or orthopedic surgeries • With FloSeal ® , decreased risk of blood product transfusion, shorter surgery time and decreased product usage in spine surgeries compared to control group (Surgiflow, a flowable gelatin matrix with thrombin) • Risk of complications and hospital length of stay did not differ • No difference in time to hemostasis between FloSeal ® and Surgiflow for patients under laminectomy or laminoarthrectomy with a bleeding not responding to standard hemostatic techniques Hemostasis in neurosurgical surgery 136 • Shorter surgery duration, lower estimated blood loss, shorter hospital stays, fewer intensive care unit days and shorter time-to-recovery with FloSeal ® than with the local bleeding control guidelines • No patient with FloSeal ® required blood transfusion compared to the control, where in 5 units were administered Hemostasis in ear-nose-throat (ENT) surgeries [137][138][139] • Hemostasis successful in all the application sites and no reported intraoperative complications during endoscopic sinus surgery • Use of FloSeal ® during thyroidectomy showed reduction of the mean operating time and an earlier wound drain removal, resulting in shorter postoperative hospital stay • No difference of postoperative morbidity between the two groups • During tonsillectomy, improved wound healing, a trend for less postoperative pain, a shorter duration of pain-medications use and reduced pain-medication consumption/demand associated with the use of FloSeal ® Hemostasis in laparoscopic cholecystectomy 140 • Shorter operating time and lower intraoperative complications rate with FloSeal ® (differences not significant) • Conversion rate in laparotomy lower with FloSeal ® • Time to drain removal and length of hospital stay were not different Hemostasis in robot-assisted laparoscopic radical prostatectomy 141 • Blood transfusion rate decreased with FloSeal ® compared to control group • FloSeal ® was associated with improvements in the difference between the immediate postoperative hemoglobin (Hb) and post-operative day 1 Hb levels as well as between the mean immediate postoperative Hb and least Hb levels CoSeal ® , Baxter Inc.…”
Section: Applicationsmentioning
confidence: 99%